A marginal structural model for recurrent events in the presence of time‐dependent confounding: non‐specific effects of vaccines on child hospitalisations. (31st August 2016) - Jensen, Aksel K. G.; Ravn, Henrik; Sørup, Signe; Andersen, Per
Abstract : Using a Danish register‐based study on childhood vaccination and hospitalisation as motivation, a marginal structural model for recurrent events is studied. The model addresses a number of challenges which may be seen more generally in large register‐based cohort studies. One is to adjust for a time‐dependent confounder when studying the effect of a time‐varying exposure on a recurrent event based on an analysis in continuous time. Another is to report results via a measure which is easy to interpret and communicate even though quite elaborate treatment regimes are considered. Lastly, the implementation of continuously updated weights implies a substantial computationally demanding workload. Copyright © 2016 John Wiley & Sons, Ltd.